Effect of composting on the microbiological and parasitic load in animal production wastes in Brazil - Paula Fernanda Alves Ferreira; Júlia Ferreira Xavier; Danielli Monsores Bertholoto; Dayanne Araújo de Melo; Thaís Ribeiro Correia; Shana de Mattos de Oliveira Coelho; Miliane Moreira Soares de Souza; Marco Antônio de Almeida Leal; Ednaldo da Silva Araújo; Irene da Silva Coelho (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Animal production wastes are promising for use in agricultural production as a plant nutrient or soil conditioner. However, if not properly managed, they can contaminate the soil and plants, resulting in public health risks. Considering that the composting technique is recommended to ensure compost hygiene and agronomic viability, the present study aimed to evaluate the microbiological and parasitic load during the composting of residues from conventional and organic animal productions. Method The presence of Salmonella sp. and/or helminth eggs and the quantification of thermotolerant coliforms were determined in horse bedding and organic and conventional poultry litter during the process of composting.  Results The initial load of thermotolerant coliforms was greater than 1017 MPN g-1 in the three raw materials. All of them showed a significant reduction in these bacteria at the end of the composting process, reaching 99.98%, 100.00%, and 99.80% in the horse bedding, organic poultry litter, and conventional poultry litter, respectively. All the fresh residues contained helminth eggs, with the horse bedding exhibiting the highest amount compared to the others. However, they all revealed an absence of helminth eggs at the end of the composting process. Salmonella sp. was absent in both the raw materials and the final compost. Conclusion Composting was effective in eliminating helminth eggs and reducing thermotolerant coliform levels. However, the final composts retained a higher pathogenic microbial load than that required by the current Brazilian legislation for use in agriculture.